2020
DOI: 10.1007/s00383-020-04748-3
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative “complications" following laparoscopic-assisted anorectoplasty: A systematic review

Abstract: Aim This study reviewed the literature on the postoperative complications following laparoscopic-assisted anorectoplasty (LAARP). Methods A Medline and Embase search was performed for the terms "anorectal malformation" (ARM) "laparoscopic" and "complication". Articles without English full text, review articles, systematic reviews, case reports, case series < 5 cases and duplicate articles were excluded. Two reviewers independently performed the eligibility assessment and data extraction. Data were collected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Firstly, the deep location of the rectal pouch and long common wall of the fistular and rectum increases the difficulty of transabdominal/laparoscopic dissection, leading to a high risk of urethral diverticulum. [22] The incidence of posterior urethral diverticulum appeared to be rare in recent years as distal colostogram was all carried out before repair and surgeons became proficient in PSARP. However, Peña et al reported that 20 cases of RBF developed urethral diverticulum, all of which had previously undergone the transabdominal approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the deep location of the rectal pouch and long common wall of the fistular and rectum increases the difficulty of transabdominal/laparoscopic dissection, leading to a high risk of urethral diverticulum. [22] The incidence of posterior urethral diverticulum appeared to be rare in recent years as distal colostogram was all carried out before repair and surgeons became proficient in PSARP. However, Peña et al reported that 20 cases of RBF developed urethral diverticulum, all of which had previously undergone the transabdominal approach.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] Finally, the value of LAARP on bowel function has been questioned, owing to the short follow-up and subjective parameters of the scores. [22]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] The LAARP for RPUF is known to have rectal prolapse in 14.08% and a posterior UD in 3.02% of patients. [ 14 ] The higher propensity of the UD is peculiar to RBUF, unlike RPUF where fistula management is relatively easier with a laparoscopic approach and has proved to be safe. [ 15 ] MRI is more sensitive than cystoscopy and voiding cystourethrogram (VCUG) to detect UD as the urethral side of the fistula gets sealed, and the UD does not communicate with the urethra.…”
Section: Discussionmentioning
confidence: 99%
“…Common postoperative complications of ARM repair include rectal prolapse, remnant of the original fistula, anal or rectal stricture, wound dehiscence, and recurrent fistula. 1 A cloacal malformation is characterized by a single perineal orifice in which the urologic, gynecologic, and gastrointestinal tracts meet. It represents one of the most complex congenital anomalies of the pelvic organs in females, with an incidence of 1 in 50,000 births.…”
Section: Introductionmentioning
confidence: 99%